2017
DOI: 10.1186/s12876-016-0567-4
|View full text |Cite
|
Sign up to set email alerts
|

The cut-off value of tumor size and appropriate timing of follow-up for management of minimal EUS-suspected gastric gastrointestinal stromal tumors

Abstract: BackgroudThe detectable rate of minimal gastric GISTs has continuously increased. While the surveillance and management of GIST <2 cm have been deemed controversial or lack evidence-based approaches.  The aim of the current study is to propose a cut-off value of tumor size for treatment policy and the appropriate timing for endoscopic ultrasonography (EUS) follow-up in the minimal EUS-suspected gastric GIST patients.MethodsA single-institution retrospective study was performed. 69 patients with EUS-suspected g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 21 publications
0
32
1
Order By: Relevance
“…If EUS imaging of a SEL with an endoscopically negative biopsy shows a hypoechoic solid mass of > 1 cm, subsequent EUS-FNA is needed to obtain a conclusive tissue diagnosis of a GIST[ 21 , 56 ]. Small SELs of < 1 cm are currently recommended to undergo periodic EUS follow-up (every 6 mo or 1 year)[ 56 , 91 ] because EUS-FNA for small SELs of < 1 cm is technically difficult. These aggressive approaches for early diagnosis and early treatment of small SELs, similar to the approaches for gastrointestinal tract cancer, seem to be the only promising way to improve patients’ quality of life and prognosis.…”
Section: Management Of Small Sels Suspected To Be Gistsmentioning
confidence: 99%
“…If EUS imaging of a SEL with an endoscopically negative biopsy shows a hypoechoic solid mass of > 1 cm, subsequent EUS-FNA is needed to obtain a conclusive tissue diagnosis of a GIST[ 21 , 56 ]. Small SELs of < 1 cm are currently recommended to undergo periodic EUS follow-up (every 6 mo or 1 year)[ 56 , 91 ] because EUS-FNA for small SELs of < 1 cm is technically difficult. These aggressive approaches for early diagnosis and early treatment of small SELs, similar to the approaches for gastrointestinal tract cancer, seem to be the only promising way to improve patients’ quality of life and prognosis.…”
Section: Management Of Small Sels Suspected To Be Gistsmentioning
confidence: 99%
“…Most of small GISTs were discovered incidentally. Although most small GIST or micro-GIST show benign or indolent clinical course, there are still very few cases showing aggressive behavior, especially those tumors with high mitotic counts ( 26 ).…”
Section: Principles Of Pathologic Diagnosismentioning
confidence: 99%
“…However, studies found that some GGs < 2 cm would enlarge after years of follow-up. 26,27 biomarker to evaluate the effect of therapy and postoperative surveillance. Small GGs are often negative on CT scans and endoscopy.…”
Section: Discussionmentioning
confidence: 99%